2005
DOI: 10.1021/jf0502045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maillard Reaction on Allergenicity of Scallop Tropomyosin

Abstract: Scallop tropomyosin (TM), the major allergen of shellfish, was prepared from adductor muscles and reacted with four reducing sugars to investigate the effect of the Maillard reaction on the allergenicity of TM. The IgE-binding ability of TM increased significantly with the progress of the reaction with glucose, ribose, and maltose, but not with maltotriose. The allergenicity was enhanced at the early stage of the Maillard reaction, and the trend of the effect depended on the type of reducing sugar used. 2,4,6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 22 publications
2
84
0
2
Order By: Relevance
“…However, some studies have demonstrated modulation oflgE recognition to tropomyosin due to heat-induced Maillard reaction, which may occur in some shellfish species (Nakamura et al 2005(Nakamura et al , 2006 According to the AllFam database, the TM f a mily is the largest "food" aller gen f a mily in animal sources, consisting of currently 47 identified TMs, mostly from crustacean species (Radauer et al 2008). Examples of well-characterized TM are Pen m 1, Pen a 1, Lit v 1, and Hom a 1.…”
Section: Structure and Biological Functions Of Shellfish Allergensmentioning
confidence: 99%
“…However, some studies have demonstrated modulation oflgE recognition to tropomyosin due to heat-induced Maillard reaction, which may occur in some shellfish species (Nakamura et al 2005(Nakamura et al , 2006 According to the AllFam database, the TM f a mily is the largest "food" aller gen f a mily in animal sources, consisting of currently 47 identified TMs, mostly from crustacean species (Radauer et al 2008). Examples of well-characterized TM are Pen m 1, Pen a 1, Lit v 1, and Hom a 1.…”
Section: Structure and Biological Functions Of Shellfish Allergensmentioning
confidence: 99%
“…However, these observations may be complicated by the fact that peanut allergens leach out of peanuts during boiling, lowering the residual allergen content in the boiled nuts (Mondoulet et al, 2005). Maillard modification has also been found to increase the IgE-binding capacity of the allergenic shellfish tropomyosin (Nakamura et al, 2005). Individuals may have become sensitised to glycated tropomyosin itself, through consumption of the dried fish products frequently used, especially in oriental cuisine.…”
Section: Processing Induced Chemical Modification Of Allergensmentioning
confidence: 99%
“…Effects of sugar-protein or Maillard reaction on the allergenic property or IgE binding to allergens from shrimp [18], milk [19], buckwheat [20] and peanuts [11][12][13] have been studied. In the latter three studies (peanuts), increased IgE binding has been reported.…”
Section: Ige Binding Of Ribose-treated Peanut Extracts In Elisamentioning
confidence: 99%